2011
DOI: 10.1109/jsen.2010.2074193
|View full text |Cite
|
Sign up to set email alerts
|

Mass Loading in Coupled Resonators Consisting of SU-8 Micropillars Fabricated Over SAW Devices

Abstract: Surface acoustic wave (SAW) sensors extensively employ mass loading effect of a sensing film coated over the surface of a SAW device. We report experimental and simulation results of mass loading by SU-8 micropillars (in place of sensing film) attached normal to the surface of SAW resonators. For certain size of micropillars, we have observed an increase in the resonance frequency of the resonator, in contrast to the decrease in the resonance frequency normally caused by mass loading. The SAW resonator and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…In order to study the sensitivity of both wave modes to mass loading caused by thin film made of polymer material other than PMMA, the simulation is repeated for SU-8 film in place of PMMA in the simulation geometry (see Figure 1). It should be noted that SU-8 is well known for its rigidity and use in fabrication of high aspect ratio structures [8,21]. The material constants of SU-8 used in the simulation are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the sensitivity of both wave modes to mass loading caused by thin film made of polymer material other than PMMA, the simulation is repeated for SU-8 film in place of PMMA in the simulation geometry (see Figure 1). It should be noted that SU-8 is well known for its rigidity and use in fabrication of high aspect ratio structures [8,21]. The material constants of SU-8 used in the simulation are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The study also suggest suitable processing conditions for the sensing layer on the SAW device substrate to obtain the desired sensing response of the SAW sensor [7]. More recently it is reported that the mass loading sensitivity in SAW sensors can be increased by employing high aspect ratio pillars as sensing medium in SAW sensors [8,9]. In this paper, we present higher mass loading sensitivity of a SAW sensor employing Sezawa wave mode for its device operation.…”
Section: Introductionmentioning
confidence: 95%
“…Ramakrishnan et al [43] used the FE simulation to investigate coupled resonance effect by using high aspect ratio palladium nanopillars on a SAW device for hydrogen detection. Experimental and simulation results of mass loading by SU-8 micropillars made on the surface of SAW resonators have also been reported in [44].…”
Section: Coupled Resonancementioning
confidence: 99%
“…Away from coupled resonance, at h ZnO = 800 nm, Z sac and σ values remain below 0.6 and 0.1 MPa, respectively. The contact stiffness between nanorod and device surface is proportional to the area-averaged stress at the interface [44]. At coupled resonance, elastic loading occurs and a further increase in the height of the nanorods, raise the effective stiffness of the contact between nanorods and SiO 2 surface rather than its mass.…”
Section: Effect On Mass Sensitivity and Acoustic Impedancementioning
confidence: 99%
“…We use this approach to perform analyte detection measurements with a network analyzer; however, this can be done using a simple and inexpensive phase measurement circuit that outputs an analog signal representing the phase-shift. 39,40 THM analyte characterization.-We tested the absorption properties of the NPC-coated SAW devices by injecting into a separation column precise quantities of either chloroform alone or mixtures of all four THMs simultaneously: chloroform (CF), dichlorobromomethane (DCBM), dibromochloromethane (DBCM), and bromoform (BF). Standard solutions were prepared using individual THMs as gravimetric serial dilutions using a chlorobenzene solvent.…”
mentioning
confidence: 99%